What's Banking Sector Concentration Got to Do with Private Equity Market? - Oleg Badunenko; Saloni Deva; Dorothea Schäfer; Michael Viertel (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
The paper investigates the link between bank concentration and a country's buyout market. We perform a macro level analysis for 15 European countries during 1997-2007. We estimate the elasticity of the country i's buyout market to country i's concentration in the banking sector. Our major finding suggests that the more concentrated the banking sector is, the better it is for the size of the buyout market. The elasticity ranges from 1 up to 3 percent depending on which bank concentration measure is employed and what segment of buyout market we look at. We also find that bank concentration is irrelevant for the average deal size. To the best of our knowledge, this is the first paper to analyze the link between banking sector developments and the market for leveraged buyouts.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: M14; G24; G34; 330; Private equity financing; corporate finance; banking concentration; market power; banking competition